DIAGNOSTIC VALUE OF PELVIC FLOOR ULTRASONOGRAPHY FOR DIAGNOSIS OF PELVIC ORGAN PROLAPSE - Orazov Mekan,; Lokshin Vyacheslav,; Toktar L.R.,; Khamoshina M.B.,; Gevorgian D.A.,; Dostieva Sh.M.,; Markina Y.V.,; Lologaeva M.S.,; Karimova G.A., (Scientific Journal of Pedagogy and Economics, 2020)
Female pelvic floor dysfunction encompasses a number of prevalent clinical conditions, including female pelvic organ prolapse, urinary and fecal incontinence, obstructed defecation, and sexual dysfunction. Pelvic Organ Prolapse (POP) is the hidden epidemic. In the USA it has been conservatively estimated that the prevalence of symptomatic POP will increase by 46% to reach 4.9 million women by 2050. POP is a major public health issue that will continue to grow in developed countries due to the aging populations. Prolapse development is multifactorial, with vaginal child birth, advancing age, and increasing body-mass index as the most consistent risk factors. The integrated lifespan model presented by De Lancey describes predisposing and inciting causal factors for the development of POP where childbirth is considered an important inciting factor. Patients generally present with several complaints, including bladder, bowel, and pelvic symptoms; however, with the exception of vaginal bulging, none is specific to prolapse. Women with symptoms suggestive of prolapse should undergo a pelvic examination. Physical exam (PE) remains the primary modality to evaluate POP, but clinical examination alone is not enough diagnosing pelvic floor dysfunction. The International Continence Society Pelvic Organ Prolapse Quantification (ICS POP-Q) system provides information on surface anatomy only and gives no information on underlying organs or functional anatomy. It can lead to underestimate or misdiagnose the site, degree, and nature of visceral prolapse of pelvic organ prolapse in 45–90% of patients and caused result in incorrect treatment and recurrence of symptoms in 10–30% of patients after surgery. The diagnosis of prolapse of the posterior vaginal compartment, which gynecologists call posterior vaginal wall descent a ‘rectocele’, this appearance may be caused by at least five distinct anatomical conditions which are difficult to distinguish without imaging. These include true radiological rectocele, perineal hypermobility, enterocele, rectoenterocele, and rectal intussusception. Imaging can identify conditions that mimic cystocele, such as urethral diverticula or Gartner cysts, and also can show two types of cystoceles with different functional implications. Therefore, we are needed additional diagnostic tools to make qualified decisions on conservative or surgical treatment. Transperineal sonography is the least invasive, cheapest, simplest, and most commonly available method for pelvic floor imaging. In addition, it has tremendous potential to be used as a research tool in trying to understand the pathophysiology of POP. Childbirth is significantly associated with develop by urinary incontinence(UI) and POP. Levator avulsion is the traumatic disconnection of the puborectalis component of the levator ani from the os pubis. Levator avulsion injury may occur during vaginal delivery, and forceps delivery carries a higher risk of trauma to the pelvic floor muscles than vacuum and normal vaginal delivery. Childbirth-related morphological abnormalities or defects of the puborectalis muscle (“avulsion”) can be diagnosed not only by three-dimensional (3D) ultrasound but by 2D translabial ultrasound too. Enlarges the levator hiatus (LH), levator-urethra gap (LUG) as measured by 3-dimensional transperineal tomographic ultrasound are also associated with development of POP. Thus, transperineal ultrasound is one of the most reliable and effective methods for diagnosing pelvic floor injuries and dysfunction.